PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA MELALUI MODEL PROJECT BASED LEARNING BERBANTUAN MS. EXCEL DI KELAS XI SMA ASY-SYAFI’IYAH INTERNASIONAL MEDAN - siti maysarah (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The purpose of this research is to analyze: (1) Is the increase creative thinking mathematics of the students who obtain a Project Based Learning model assisted by Ms.Excel higher than the ability of mathematics creativity of students who received regular learning. (2) Is there an interaction between students’ mathematics ability (high, medium, low) and model of learning to increase students’ creative thinking mathematics ability. (3) How is the students’ answering process in solving the problem of creative thinking mathematics ability in learning using Project Based Learning model assisted by Ms.Excel and regular learning. This type of research is a quasi experimental research. The data in this study were analyzed using descriptive statistical and inferential analysis. Descriptive analysis is intended to describe the percentage of achievement scores of students in learning by using a Project Based Learning model assisted by Ms.Excel and regular Learning. Inferential analysis of data is performed by Two Ways ANOVA. Based on those analyses, the researcher acquires the result. That are: (1) The increasing of students’ creative thinking mathematics ability using Project Based on Learning model assisted by Ms.Excel is higher than regular learning. (2) There is no interaction between mathematical prerequisite ability and model of learning on creative thinking mathematics ability. (3) Students’ answering process that taught by Project Based Learning model assisted Ms.Excel is better than students’ answering process that taught by regular learning.